The influence of substrate, urea supplementation, and liming on the yield and antioxidant activities of Pleurotus sajor-caju M2345 and Pleurotus ostreatus M2191 - Tirngo Begashaw; Asmamaw Tesfaw (Kuwait Journal of Science)
Pleurotus species are grown because of their high yield potential, high nutritional and therapeutic value, and ease of growth. This research aimed to evaluate the yield and antioxidant activities of Pleurotus sajor-caju M2345 and Pleurotus ostreatus M2191 grown on different lignocellulosic substrates, including crop weeds, hairy willow herbs, cottonseeds, and water hyacinth. The growing media were made from 90 % substrates, 8 % wheat bran, and 2 % gypsum. The effects of supplementation with urea and calcium carbonate on the yield and antioxidant activities of oyster mushrooms were also investigated. The highest total yield and biological efficiency for P. sajor-caju M2345 and P. ostreatus M2191 were 870.31 g, 145.1 %, and 641.87 g, 107 %, respectively, on 25 % hairy willow herb waste and 75 % cottonseed waste during the dry season. The lowest total yield and biological efficiency of P. ostreatus M2191 and P. sajor-caju M2345 were obtained from T5 (75 % weed+25 % cottonseed). The best lime and urea concentrations for improving the yield of the Pleurotus species were 4 % and 1 %, respectively. The Pleurotus species grown with 100 % cottonseed waste (T1) and an equal ratio of hairy willow herb to cotton seed presented the highest DPPH free radical scavenging activity. This study provides novel insights into the synergistic effects of liming, urea addition, and agricultural residues as substrates for sustainable Pleurotus production and highlights the combined role of substrate composition and supplementation in enhancing the yield and antioxidant activities of oyster mushrooms. The findings contribute to the development of cost-effective and eco-friendly strategies for mushroom cultivation.